Performance of oyster mushroom species in the summer season using spore culture and vegetative tissue culture methods: Performance of oyster mushroom in tissue culture (SAARC Journal of Agriculture, 2022)
Performance of four oyster mushroom species such as Pleurotus ostreatus, PO-2 (S1), P. djmour, Pop-1 (S2), P. florida, FLO-2 (S3) and Pleurotus ostreatus PO-10 (S4) with two culture methods like spore culture (C1) and vegetative tissue culture (C2) was investigated. The experiment was conducted in Mushroom Development Institute (MDI), Savar, Dhaka from April to June, 2021 in CRD method. Considerable variations on different parameters related to growth and yield attributes were recorded.The least time required (56 days) from pure culture to first harvest was recorded in S2. The minimum days required for mycelium running completion in spawn packet (20.25 days) was observed from the treatment combination S2C1 whereas the maximum days (28.5 days) was observed from S3 C2. From pure culture to first harvest, the highest duration (77.75 days) was observed in S1C2 and the lowest duration (54.50 days) was observed in S2C1. The diameter of pilea ranged from 6.2 cm to 7.3 cm with significant difference. The maximum yield (137.25g) and biological efficiency (61%) were achieved from S2C1, the lowest yield (108.12g) and biological efficiency (48.05%) were being found with S3C1. The protein percentage was found highest (24.56%) in S1 and fiber was maximum (20.72%) in S3. Protein percentage was found maximum (24.82%) in S1C1 and minimum (21.52%) in S3C2. The highest yields (133.31 g, 124.47 g and 137.25 g) were achieved from S2 species, C1 culture method and combination treatment S2C1, respectively.SAARC J. Agric., 20(2): 169-181 (2022)